482 Spontaneous Pneumomediastinum Case Series: Lessons Learnt in Assessment and Management. (19th August 2022) - Manku, B; Krishnamoorthy, A; Thomson, L; McLaughlin, E
Abstract: Aim: Spontaneous pneumomediastinum (SPM) is usually a self-limiting condition in clinically stable patients with no obvious causative factor. SPM can be difficult to distinguish from important secondary causes such as tracheobronchial injury or oesophageal perforation. Therefore, thorough clinical history and examination is of paramount importance. We aim to highlight lessons learnt from our experience to improve rapid diagnosis and clinical management of these patients. Method: Patients were identified through hospital records between October 2019 – December 2021. Data was collected on clinical presentation, precipitating events, radiological confirmation of SPM and compared with current reported literature. Results: 11 patients were identified, 8 males (72.7%), 3 females (27.3%) with a mean age of 29 + 17 years. The most frequent symptom was retrosternal chest pain 27.3%; and vomiting the most common precipitating event (54.5%). Mean white cell count was 14×10 9 /l on admission. All patients underwent plain film chest radiography, and subsequent computerised tomography of thorax, abdomen and pelvis. Patients underwent gastroscopy selectively, showing no acute pathology. Mean length of stay was 4.6 days. No patients required operative intervention or any other intervention beyond antibiotics. No complications or recurrence were found in patients at follow up. Conclusion: SPM is a self-limiting condition with low morbidity and mortality. If life-threatening causes have been excluded, SPM can safely be managed expectantly at a local level, without the need of transfer to tertiary centres and prolonged hospital admission. We propose a structured approach to aid in the management of SPM and help address these challenges.